2017
DOI: 10.1002/adfm.201704169
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous NC@CuCo Nitride Nanosheet Networks: Highly Efficient Bifunctional Electrocatalyst for Overall Water Splitting and Selective Electrooxidation of Benzyl Alcohol

Abstract: Highly active and stable bifunctional electrocatalysts for overall water splitting are important for clean and renewable energy technologies. The development of energy-saving electrocatalysts for hydrogen evolution reaction (HER) by replacing the sluggish oxygen evolution reaction (OER) with a thermodynamically favorable electrochemical oxidation (ECO) reaction has attracted increasing attention. In this study, a self-supported, hierarchical, porous, nitrogen-doped carbon (NC)@CuCo 2 N x /carbon fiber (CF) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 307 publications
(192 citation statements)
references
References 56 publications
6
185
0
1
Order By: Relevance
“…[17] There is no peak in the Raman spectrum of Ni 3 Ns ample in the Raman shift range of 1200 cm À1 to 1800 cm À1 (Figure 2b). [17] There is no peak in the Raman spectrum of Ni 3 Ns ample in the Raman shift range of 1200 cm À1 to 1800 cm À1 (Figure 2b).…”
Section: Angewandte Chemiementioning
confidence: 93%
See 1 more Smart Citation
“…[17] There is no peak in the Raman spectrum of Ni 3 Ns ample in the Raman shift range of 1200 cm À1 to 1800 cm À1 (Figure 2b). [17] There is no peak in the Raman spectrum of Ni 3 Ns ample in the Raman shift range of 1200 cm À1 to 1800 cm À1 (Figure 2b).…”
Section: Angewandte Chemiementioning
confidence: 93%
“…Forschungsartikel ulting from the first-order scattering of the E2g mode of sp 2 carbon domains. [17] There is no peak in the Raman spectrum of Ni 3 Ns ample in the Raman shift range of 1200 cm À1 to 1800 cm À1 (Figure 2b). On the contrary,the Raman spectrum of Ni 3 N@C exhibits two peaks at 1590 and 1359 cm À1 ,s uggesting the existence of carbon in the hybrid material.…”
Section: Angewandte Chemiementioning
confidence: 93%
“…This result demonstrates that the coupling of Ni and Mo 2 C promotes the formation of small sized Ni and Mo 2 C NPs. [56] In addition, with the increment of Ni content, the I D /I G value decreases gradually. [26] Because the proportion of Mo 2 C in Ni/Mo 2 C(1:2)-NCNFs is the largest compared to other samples, all the characteristic peaks of Mo 2 C can be observed in the XRD patterns.…”
Section: Morphological and Structural Characterizationsmentioning
confidence: 99%
“…have attributed the good performance of NiCoP structure to favorable electronic states resulting from the synergistic interplay between nickel and cobalt . Zheng et al have revealed that the adsorption energies of key species can be modulated due to the synergistic effect between Co and Cu in CoCuN catalysts . Liang et al have suggests that construction of bimetallic compound could effectively alter the electronic structure tune the hydrogen (or water) adsorption energy, thus dramatically enhance the catalytic activity .…”
Section: Resultsmentioning
confidence: 99%